Microstructural Characterization and Mechanical Properties of Iron Reinforcements in Buildings from the Medieval and Modern Periods in France. Issue 3 (3rd April 2019) - L'Héritier, M.; Guillot, I.; Dillmann, P.
ABSTRACT: This article presents an overview of the metallographic structures observed on the iron reinforcements of more than 20 buildings from the medieval and modern period in France, which are representative of the evolution of ironmaking techniques at that time (330 samples). Metallographic examinations show a great diversity of structures, even in the same sample: pure ferritic iron to low pearlitic steel, presence of phosphorus in solid solution (locally up to 0.5%wt), numerous slag inclusions of various sizes, porosities. Tensile tests were performed on a representative set of samples from 4 buildings (46 samples). The results are in accordance with the metallographic observations: mechanical behaviors are very heterogeneous, even in samples taken on the same artefact. Failure happened at values as low as the yield stress up to 25% of the plastic strain. These reinforcements probably worked in the elastic domain at low stress (<150 Mpa). These mechanical properties are significantly beyond those of modern carbon steels and question the exact role of iron in the stability of monuments.